2017
DOI: 10.1080/13621718.2016.1249644
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical property characterisation of aluminium–steel joints fabricated using ultrasonic additive manufacturing

Abstract: Driven by the interest to weld steel and aluminium (Al) in the solid state to prevent intermetallic formation, 9 kW ultrasonic additive manufacturing (UAM) has been used to fabricate Al 6061-4130 steel dissimilar metal builds. In addition, Al 6061-6061 builds were fabricated using similar techniques to provide a baseline for mechanical property measurement. Mechanical testing performed using pushpin testing shows that steel-Al dissimilar metal welds fail across multiple layers while Al-Al welds delaminate from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…As expected, the resulting microstructure and mechanical properties would be affected by the UAM process parameters. For this reason, a significant part of the literature on UAM paid more attention to optimization of the process parameters [29,34,40,44] and microstructural analyses [12,22,28,45,46] of the as-built part. e microstructural analyses provide substantial information about the bonding mechanism, grain refinement, and defects, which are highlighted in the next section.…”
Section: % Lwd �mentioning
confidence: 99%
See 4 more Smart Citations
“…As expected, the resulting microstructure and mechanical properties would be affected by the UAM process parameters. For this reason, a significant part of the literature on UAM paid more attention to optimization of the process parameters [29,34,40,44] and microstructural analyses [12,22,28,45,46] of the as-built part. e microstructural analyses provide substantial information about the bonding mechanism, grain refinement, and defects, which are highlighted in the next section.…”
Section: % Lwd �mentioning
confidence: 99%
“…Higher load and larger area under the curve correspond to better push-pin performance. Sridharan et al [22] reported the push-pin testing performance of Al6061-T6 foils on annealed 4130 steel (Al6061-4130) and Al-Al (Al6061-6061) builds. is was attributed to the high plastic flow at the interface resulting in oxide removal and asperity collapse, improving the metallurgical bonds and the mechanical properties.…”
Section: Push-out Testmentioning
confidence: 99%
See 3 more Smart Citations